Diversity, prevalence and host specificity of avian parasites in southern Tunisian oases. Issue 7 (23rd November 2017) - Ayadi, Tasnim; Selmi, Slaheddine; Hammouda, Abdessalem; Reis, Sandra; Boulinier, Thierry; Loiseau, Claire
Abstract: Oases are semi-natural woodlots surrounded by an inhospitable desert environment. This insular-like habitat system is known to support a mixture of sedentary and migratory bird species originating from different areas. However, little is known about the interactions between these birds and parasites. In this study, we investigated the diversity, prevalence and host specificity of avian haemosporidian parasites in southern Tunisian oases in two sedentary and common bird species, the laughing dove Spilopelia senegalensis and hybrid sparrow Passer domesticus × hispaniolensis, in six sites that differ regarding vegetation structure and distance to the coast. Two new Haemoproteus lineages, related to other Haemoproteus transmitted by biting midges, were detected in doves. With regard to sparrows, all detected parasites have previously been reported in other sparrow populations, except for one new Haemoproteus lineage. Our results also showed that densely vegetated sites were characterized by the higher prevalence of Plasmodium but a lower prevalence of Haemoproteus compared with less-vegetated sites. This is the first study aiming to explore avian parasites in the oasis habitat. Gathering data on a larger sample of oases with different sizes and isolation levels will be the next step to better understand factors shaping the transmission dynamics of avian parasites in such ecosystems.